Pengaruh Media Gambar Wayang Terhadap Motivasi Dan Pemahaman Siswa Pada Mata Pelajaran PPKN UPTD SD Tengket 1 Arosbaya - ulya, Sarifatul; Arifin, Zainal (Penerbit STKIP PGRI Bangkalan, 2025)
This Citizenship Education learning is still conventional, or teacher centre, so it can cause problems faced by teachers such as class conditions where students feel bored and crowded during learning, student motivation during learning is low which can result in students' lack of understanding when working on questions. Puppet Image Media is a suitable medium for solving learning problems, students are more enthusiastic when learning and also understand learning more easily. The aim of this research is to determine the effect of wayang image media on students' motivation and understanding in PPKN class 2 UPTD SD Tengket 1 Arosbaya subjects. The research method used is quantitative using the One-Group Pretest-Posttest Design type. The results of the research show that wayang image media has a significant effect on students' motivation and understanding based on the results of the first test analysis, namely the paired sample t-test with sig values. of 0.000 < 0.05 for motivation, while for understanding the value of sig. equal to 0.000 < 0.05. Next, the second test is the Manova test with a sig value. equal to 0.000 < 0.05. So there is a simultaneous influence of wayang image media on motivation and understanding.